2016
DOI: 10.1179/2295333715y.0000000073
|View full text |Cite
|
Sign up to set email alerts
|

Isolated acquired factor VII deficiency: review of the literature

Abstract: Acquired FVII deficiency has been reported in 42 patients. There are well-established clinical diseases associated with acquired FVII deficiency, most notably infections, malignancy and haematological stem cell transplantation. The exact pathogenesis of the diseases is still unknown, but different pathophysiological hypotheses have been suggested. The clinical manifestation of acquired FVII deficiency varies greatly in severity; asymptomatic course as well as severe life-threatening bleeding diathesis and fata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…It is well known that PT is prolonged by a series of conditions, including direct acting anticoagulants (among them argatroban, dabigatran, rivaroxaban, apixaban, edoxaban)[29] and intake of vitamin K antagonists[30], vitamin K deficiency[31], coagulation factor deficiency, lupus anticoagulans[32], polycitemia vera[33]. Similarly, it was shown that factor VII deficiency is frequent in patients with infections, neoplasia, trauma, nephrotic syndrome, left heart failure, penicillin intake and clearly in patients under vitamin K dependent anticoagulation[34, 35]. However, ATIII should only be altered due to mutations[36], consumption[37] or hepatocellular dysfunction[38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that PT is prolonged by a series of conditions, including direct acting anticoagulants (among them argatroban, dabigatran, rivaroxaban, apixaban, edoxaban)[29] and intake of vitamin K antagonists[30], vitamin K deficiency[31], coagulation factor deficiency, lupus anticoagulans[32], polycitemia vera[33]. Similarly, it was shown that factor VII deficiency is frequent in patients with infections, neoplasia, trauma, nephrotic syndrome, left heart failure, penicillin intake and clearly in patients under vitamin K dependent anticoagulation[34, 35]. However, ATIII should only be altered due to mutations[36], consumption[37] or hepatocellular dysfunction[38, 39].…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 Other rare etiologies of acquired factor VII deficiency include cases secondary to administration of penicillins, cephalosporins and diseases such as myeloma, underlying malignancy and usage of anti-thymocyte globulin and IL- 2. 10 , 11 The levels of factor VII in previous cases presenting with severe hemorrhage were between <1% to 38% of normal factor VII levels. 11 Additionally, factor VII levels have been measured in the setting of decompensated cirrhosis with mean level of 40%, which is significantly lower than than levels in patients with compensated cirrhosis, obstructive jaundice, and noncirrhotics with alcoholic liver disease.…”
Section: Discussionmentioning
confidence: 94%
“…If symptomatic patients usually have umbilical stump bleeding, skin and mucosal tract hemorrhage[72].FVII is a 50 Kda single chain polypeptide encoded by F7 gene located on chromosome 13 and FVII levels are influenced by age, sex and health condition such as blood cholesterol and triglyceride levels[73,74]. FVII deficiency is observed in 1 in 500,000, with variable phenotypes[74]. Some patients do not show bleeding phenotype despite very low FVII levels, whereas others with similar FVII antigen levels show severe bleeding phenotype[74].…”
mentioning
confidence: 99%
“…FVII deficiency is observed in 1 in 500,000, with variable phenotypes[74]. Some patients do not show bleeding phenotype despite very low FVII levels, whereas others with similar FVII antigen levels show severe bleeding phenotype[74]. The bleeding phenotypes of FVII deficiency include central nervous system hemorrhage, epistatic and menorrhagia[74].…”
mentioning
confidence: 99%
See 1 more Smart Citation